Activity-based Learning and Development of High Mental Abilities an Intention of Intermediate Level Chemistry Syllabus - Swehra Moeed (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
Course content is a hub of educational activities. The method of teaching and assessment procedure more or less rely on the nature of syllabus. Being core of educational activities great importance is given to course content.Ã‚Â  This study was conducted to investigate the opinion of teachers concerning existing syllabus of intermediate level chemistry subject. The data was gathered through questionnaire based on 5 point Likert scale items. Sixty three teachers of chemistry subject were working at Government Degree Colleges (GDCs) and Government Higher Secondary Schools (GHSSs) of district Peshawar. Among sixty three fifty seven teachers were selected randomly as sample of study. The collected data prevail that the implemented syllabus is mostly based on theory, hence in such circumstance the national aim to produce skill generation as per demand of market seem impossible. The condition of practical work and hand on activities is dispiriting in government educational institutes. The psychological and social need of students has been ignored while designing the syllabus. The text book is a mean of imparting pre-set information, it seems failed to provide valuable engaging activities.